2022
DOI: 10.1108/jrf-08-2022-0216
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of green bond market development in Asian economies

Abstract: PurposeIn the recent decades, the green projects have suffered from serious lack of investment, highlighting the major role of green financing to attract private investors to these projects. The main purpose of this paper is to explore the economic impacts of green bond (GB) market in 37 Asian economies.Design/methodology/approachTo empirically analyze the impacts of issued GBs on different macroeconomic variables of 37 Asian countries, the co-integration and causality approaches are employed to analyze the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Researchers have studied how nations might maximize economic gains from natural resources while reducing environmental harm. Addressing sustainable economic development concerns requires this area [86,101,146,166].…”
Section: Green Finance and Economymentioning
confidence: 99%
“…Researchers have studied how nations might maximize economic gains from natural resources while reducing environmental harm. Addressing sustainable economic development concerns requires this area [86,101,146,166].…”
Section: Green Finance and Economymentioning
confidence: 99%
“…Phung Thanh (2022) investigates how the growth of the green bond market has affected Asian economies economically. Study findings indicated that the market for green bonds is growing and positively influences economic indicators such as GDP growth, employment, and investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These policies focus on the trajectory of the industrial growth pattern that is shaping the trajectory of the climatic shift, and thus, the need to balance the importance of growth and profitability of a firm, along with other societal goals (Wilson et al, 2003). Accordingly, venturing into climate-friendly investing has witnessed increasing interest attributable to investors' choice to apply social, environmental and governance lenses to their investments (Phung Thanh, 2022;Rehman et al, 2022;Paek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…, 2003). Accordingly, venturing into climate-friendly investing has witnessed increasing interest attributable to investors' choice to apply social, environmental and governance lenses to their investments (Phung Thanh, 2022; Rehman et al. , 2022; Paek et al.…”
Section: Introductionmentioning
confidence: 99%